The Life of the Weevil - Fabre, Jean-Henri, 1823-1915; Teixeira de Mattos, Alexander, 1865-1921 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Life of the Weevil" by Jean-Henri Fabre and Alexander Teixeira de Mattos is a scientific publication written in the late 19th century. The book is an exploration of various species of weevils, detailing their biology, behavior, and interplay with their environments. It specifically focuses on Fabre's meticulous observations, illustrated across different chapters, inviting readers into the intricate lives of these insects. The opening of the book sets a reflective tone, as Fabre discusses his passion for numismatics and fossil records, drawing parallels between the history engraved in coins and the stories told through the study of insects. He introduces his exploration of weevils within a geological context, emphasizing how they, along with their surroundings, speak volumes about past ecosystems. The beginning illustrates the intertwined lives of weevils and their plants, particularly highlighting the relationship between various species of thistles and weevils like the Spotted Larinus. Fabre$1 (Bs detailed observations promise a wealth of insight into the natural world, making this a captivating read for those interested in entomology and the beauty of small wonders. (This is an automatically generated summary.)s
"The essays on weevils contained in the Souvenirs entomologiques."--Translator's note.
Release date is 2021-11-29
Jeroen Hellingman and the Online Distributed Proofreading Team at https://www.pgdp.net/ for Project Gutenberg (This file was produced from images generously made available by The Internet Archive)
Keywords: Beetles